IMPLEMENTATION OF PUBLIC SECTOR ACCOUNTING IN THE FINANCIAL SYSTEM OF THE EAST KUTAI REGENCY GOVERNMENT - Anggraini, Leny Susilawati; Yovita, Maria (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to examine the implementation of public sector accounting within the financial system of the East Kutai Regency Government and to assess its contribution to improving transparency and accountability in local financial governance. In the context of fiscal decentralization, East Kutai faces challenges in managing a large budget while ensuring efficiency, openness, and integrity. This research employs a descriptive qualitative approach, using in-depth interviews, document analysis, and observation as data collection techniques. The findings reveal that the application of accrual-based Government Accounting Standards (SAP), supported by information systems such as SIPD and SIMDA Keuangan, has improved the quality of financial reporting and serves as a critical foundation for public decision-making. Key success indicators—such as transparency, accountability, efficiency, and regulatory compliance—are used to evaluate local financial performance. East Kutai Regency has received an unqualified opinion (Wajar Tanpa Pengecualian, WTP) from the Audit Board of Indonesia (BPK) for ten consecutive years, reflecting its success in achieving the principles of good governance. Nevertheless, challenges remain, particularly in terms of human resource capacity and technological infrastructure. Therefore, a sustainable strategy is needed to strengthen civil service competencies and optimize local financial information systems.